2005
DOI: 10.1111/j.1744-6171.2005.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

An Internet Discussion Board for Parents of Mentally Ill Young Children

Abstract: While the study findings cannot be generalized, these results suggest that parents will use electronic discussion boards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Internet-based education and social support surpasses other traditional educational strategies in terms of its reach (potentially global) and convenience to users. 34,57,69 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internet-based education and social support surpasses other traditional educational strategies in terms of its reach (potentially global) and convenience to users. 34,57,69 …”
Section: Resultsmentioning
confidence: 99%
“…21,4857 Drawing on their shared embodied expertise, participants confirm the medical character of their problem and its remedy, and they empower each other to search for physicians who will recognize and treat their condition accordingly. 41,43 Our extensive Google search revealed an insufficient availability of discussion boards for living donor candidates and caregivers.…”
Section: The Living Donor Information Network For Caregivingmentioning
confidence: 90%
“…Scharer reviewed the status of Internet-based communication for parents caring for children with mental illness. She concluded that parents will utilize Internet-based communications 12 and that in general there is great potential for electronic communication to meet the needs of parents seeking additional support mechanisms. 13 In fact, successful Internet support systems have been implemented for a variety of populations and health states, including maternity and parenting, 14-19 cancer, 20 diabetes, 21 mental health, 22 CKD, 10 and HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Their parenting responsibilities are compounded by challenges associated with navigating mental health, school, and other systems to meet their child’s needs (Bailey, Golden, Roberts, & Ford, 2007; Yatchmenoff, Koren, Friesen, Gordon, & Kinney, 1998). They experience stigma and blame by family, friends, and their child’s school and providers because of their child’s difficulties (Oruche, Gerkensmeyer, Stephan, Wheeler, & Hanna, 2012; Scharer, 2002, 2005). Many lack needed social support and experience considerable social isolation (Lee, Anderson, Horowitz, & August, 2009; Oruche et al, 2012; Rishel et al, 2006).…”
mentioning
confidence: 99%